First-principles study of 2H-Mo2C-based MXenes under biaxial strain as Li-battery anodes - Khammuang, Satchakorn; Pratumma, Anucha; Sakulkalavek, Aparporn; Kaewmaraya, Thanayut; Hussain, Tanveer; Kotmool, Komsilp (My University, 2023)
MXenes, a family of superior 2D materials, have been intensively investigated because they have many promising properties, particularly high-performance energy storage and high flexibility. To approach the expected critical benchmarks of such materials, the strain dependence of the atomic structure is widely considered for tuning the related properties. In this work, by means of density functional theory, we demonstrate the potential application of the strained 2H phase of Mo2C-based MXenes (Mo2C and Mo2CO2) as anode materials for lithium-ion batteries (LIBs). Adsorption and diffusion of Li on the surfaces of both materials and the impact of biaxial strain (ϵb) in the range of −4% to 4% are insightfully investigated. The lowest adsorption energy of Mo2C is −0.96 eV, and that of Mo2CO2 is −3.13 eV at ϵb = 0%. The diffusion of Li ions, considering the pathway between the first two most favorable adsorption sites, reveals that the biaxial strain refinement under compressive strain decreases the energy barrier, but the induction of tensile strain increases it in both MXenes. The ranges of the energy barriers of Li-ion adsorption on the surfaces of Mo2C and Mo2CO2 are 31-57 meV and 177-229 meV, respectively. Interestingly, the storage capacity of Li can reach three layers corresponding to a comparably high theoretical capacity of 788.61 mA h g−1 for Mo2C and 681.64 mA h g−1 for Mo2CO2. The atomic configurations are stable, as verified by the negative adsorption energy as well as the slightly distorted structures, by using ab initio molecular dynamics (AIMD) simulations at 400 K. Moreover, average open circuit voltages (OCVs) of 0.35 V and 0.63 V (at ϵb = 0%) are reported for Mo2C and Mo2CO2, respectively. Furthermore, the tensile strain results in an increase in the OCVs, while compression has the opposite effect. These computational results provide some basic information on the behaviors of Li-ion adsorption and diffusion on Mo2C-based MXenes upon tuning biaxial strain. They also give a guideline on what conditions are appropriate for practically implementing these MXenes as electrode materials in LIBs.